Religius Tourism : Bless for Everyone, Now and Then in Indonesian Economics Value - Miya Dewi Suprihandari, Miya Dewi Suprihandari (Journal of Islamic Economics Perspectives, 2020)
Religion as the most important foundation of human life is also a unifying difference between humans. Between people, they are connected when some of them need some things that are not owned by some other, whatever their religion. In Indonesia, especially in areas known as the origin of several deceased religious leaders, now it has turned into a spot that is visited by many followers or groups of people of different faiths to get information as educational material for them. These conditions make the economic conditions of the area begin to change, where the surrounding community prepares everything that is expected to be able to support the changing situation and conditions. Religious tourism spot has become one of the phenomena of the emergence of economic changes in the surrounding community to grow to be more positive than the previous condition. Religious tourism is a turning point in the growth of the religious value of the community and the economic value of the surrounding community and migrant communities in the area, even regional income. To support this condition, it would be wise for the local government at the location to provide support in the form of improved suggestions and supporting infrastructure for the smooth and development of the economic conditions of the people in particular, and for local governments in general.